SMARCA4‐deficient rhabdoid tumours show intermediate molecular features between SMARCB1‐deficient rhabdoid tumours and small cell carcinomas of the ovary, hypercalcaemic type. Issue 1 (23rd June 2021) - Andrianteranagna, Mamy; Cyrta, Joanna; Masliah‐Planchon, Julien; Nemes, Karolina; Corsia, Alice; Leruste, Amaury; Holdhof, Dörthe; Kordes, Uwe; Orbach, Daniel; Corradini, Nadège; Entz‐Werle, Natacha; Pierron, Gaëlle; et al.
Abstract: Extracranial rhabdoid tumours (ECRTs) are an aggressive malignancy of infancy and early childhood. The vast majority of cases demonstrate inactivation of SMARCB1 (ECRTSMARCB1 ) on a background of a remarkably stable genome, a low mutational burden, and no other recurrent mutations. Rarely, ECRTs can harbour the alternative inactivation of SMARCA4 (ECRTSMARCA4 ) instead of SMARCB1. However, very few ECRTSMARCA4 cases have been published to date, and a systematic characterization of ECRTSMARCA4 is missing from the literature. In this study, we report the clinical, pathological, and genomic features of additional cases of ECRTSMARCA4 and show that they are comparable to those of ECRTSMARCB1. We also assess whether ECRTSMARCB1, ECRTSMARCA4, and small cell carcinomas of the ovary, hypercalcaemic type (SCCOHT) represent distinct or overlapping entities at a molecular level. Using DNA methylation and transcriptomics‐based tumour classification approaches, we demonstrate that ECRTSMARCA4 display molecular features intermediate between SCCOHT and ECRTSMARCB1 ; however, ECRTSMARCA4 appear to be more closely related to SCCOHT by DNA methylation. Conversely, both transcriptomics and DNA methylation show a larger gap between SCCOHT and ECRTSMARCB1, potentially supporting their continuous separate classification. Lastly, we show that ECRTSMARCA4 display concomitant lack of SMARCA4 (BRG1) and SMARCA2 (BRM) expression at the protein level, similar to what is seen in SCCOHT. Overall, these results expand our knowledge on this rare tumour type and explore the similarities and differences among entities from the 'rhabdoid tumour' spectrum. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.